A new BLS satellite series of net inputs to industry price indexes: methodology and uses. - Pollock, Jayson; Weinhagen, Jonathan C. (Monthly Labor Review, 2020)
This article describes U.S. Bureau of Labor Statistics efforts to develop a new set of satellite net inputs to industry price indexes that capture price change for both domestically produced and imported inputs to production. In addition to detailing the methodology for constructing the new indexes, the article discusses their publication structure and potential uses.